An integrin required for the encapsulation immune response in the tobacco hornworm, Manduca sexta L. (Lepidoptera: Sphingidae). - Levin, David Michael (Kansas State University, 2007)
Cellular encapsulation is the immune response in which insects protect themselves from multicellular parasites such as nematodes or parasitoids. During an encapsulation episode, certain insect hemocytes become attracted to a foreign invader and aggregate on its surface. In short order, the invading entity will become entrapped within a capsule comprised of thousands of hemocytes, thus rendering the parasite harmless to the insect host. Although the process of cellular encapsulation has been known for a great many years, very little knowledge yet exists regarding the biochemistry underlying capsule formation. It would seem likely that cell surface adhesion proteins mediate this immune response. In a series of in vivo encapsulation assays in the tobacco hornworm, Manduca sexta, a collection of anti-hemocyte monoclonal antibodies (mAbs) was screened for their ability to inhibit cellular encapsulation. Two of the mAbs that inhibited this immune response and incidentally specifically bind plasmatocytes, MS13 and MS34, were used to isolate a ≈ 90 kDa protein. Several short peptide sequences contained within this protein were acquired via Edman degradation. Degenerate primers based on two of these peptide sequences and total RNA from M. sexta hemocytes were used to perform RT-PCR and 5´ and 3´ RACE. This resulted in a full-length cDNA sequence of 2426 bp. A 2301 bp open reading frame within this cDNA sequence codes for a protein of 767 residues. This protein, denominated [Beta]Ms1, exhibits significant sequence homology to the [Beta]-subunits of integrins, which are a family of transmembrane, heterodimeric glycoproteins that possess adhesive properties. Analysis of recombinant segments of [Beta]Ms1 showed that the protein produced from the PCR product is the antigen to MS13 and MS34 and that these mAbs bind to the region of the integrin that contains the extracellular binding site. Northern blot analysis of various M. sexta tissues together with immunofluorescence labeling with MS13 and MS34 shows that [Beta]Ms1 is solely expressed in plasmatocytes. The totality of these experiments demonstrates that integrins are essential for the cellular immune response of encapsulation.
Keywords: encapsulation; integrin; Manduca sexta; insect cellular immunity; hemocyte; cell adhesion; Biology, Cell (0379); Biology, Entomology (0353); Chemistry, Biochemistry (0487)